Study on rot disease prevention by aerial fungicides application during the flower stage and post-harvest chitosan treatment in Chinese chestnut - LIU Yang; SUN Haitao; WANG Zhen; YU Yaxin; YU Chunxin; QIN Ling; WANG Fengchun; XING Yu (Guoshu xuebao, 2025)
[Objective] In recent years, Chinese chestnut (Castanea mollissima Blume) rot disease has shown an outbreak trend in the chestnut-producing areas of Yanshan mountain in China. The annual rate of chestnut rot disease ranges from 7% to 10%, resulting in enormous economic losses for producers and operators. Among the prevention and control measures against chestnut rot disease, the research on spraying agents during the flowering period of chestnuts still needs to continue. This study aimed to screen out effective methods for the prevention and control of chestnut rot disease. [Methods] The Yanshanzaofeng cultivar was selected as the principal experimental material within two chestnut orchards located in Qianxi County, Tangshan City, Hebei Province. Through the utilization of drones, different chemical agents were sprayed during the flowering period to select effective chenmicals suppressing internal rot disease. Furthermore, a chitosan treatment was implemented post harvest to test the inhibitory effect on the disease during storage. [Results] 3 g·L-1 azoxystrobin could significantly lower the rate of Chinese chestnut rot disease. After 4 months of cold storage, the average internal rot rate of Chinese chestnut was 2.71%, 6.42% lower than that of the control. Furthermore, there were no significant differences in the impacts on the pollination and yield indicators of Chinese chestnuts, as well as on the starch content and soluble sugar content of chestnut kernels among the different chemical treatments. In addition, the post-harvest chitosan preservation treatment could reduce the respiration intensity and internal rot rate of chestnut kernels. The chitosan preservation treatment on the chestnuts sprayed with 3 g·L-1 azoxystrobin (AJY-4) during the flowering stage could reduce the internal rot rate of chestnut kernels to 1.21% after 4 months of cold storage. Moreover, after 7 months of cold storage, the average internal rot rate of chestnut kernels was 2.40%, which was 1.90% lower than that of the control. The treatment of chitosan compound agents could significantly inhibit the occurrence of calcinosis in chestnut kernels. After 4 months of storage, the calcinosis rate of chestnut kernels with chitosan compound agent treatment was 2.14%, 2.01% lower than that of the control. After 7 months of storage, the calcinosis rate of chestnut kernels with chitosan compound agent treatment was 3.59%, 2.93% lower than that of the control. The treatment of chitosan compound agents could significantly inhibit the respiration rate of chestnut kernels as well. The treatment of chitosan compound agents did not make significant difference the quality of the chestnut kernels. [Conclusion] 3 g·L-1 azoxystrobin was capable of markedly diminishing the occurrence rate of internal rot in chestnut kernels. Moreover, this treatment did not have an adverse impact on pollination, yield, and the quality of the chestnut kernels. Concurrently, the application of chitosan compound agents before storage was effective in reducing both the respiration rate and the internal rot rate of the chestnut kernels.